Acute liver failure in a term neonate after repeated paracetamol administration - Fabio Bucaretchi; Carla Borrasca Fernandes; Maira Migliari Branco; Eduardo Mello De Capitani; Stephen Hyslop; Jamil Pedro S. Caldas; Carolina Araujo Moreno; Gilda Porta (Sociedade de Pediatria de São Paulo, 2014)
Objective: Severe hepatotoxicity caused by paracetamol is rare in neonates. We report a case of paracetamol-induced acute liver failure in a term neonate. Case description: A 26-day-old boy was admitted with intestinal bleeding, shock signs, slight liver enlargement, coagulopathy, metabolic acidosis (pH=7.21; bicarbonate: 7.1mEq/L), hypoglycemia (18mg/dL), increased serum aminotransferase activity (AST=4,039IU/L; ALT=1,087IU/L) and hyperbilirubinemia (total: 9.57mg/dL; direct: 6.18mg/dL) after receiving oral paracetamol (10mg/kg/dose every 4 hours) for three consecutive days (total dose around 180mg/kg; serum concentration 36-48 hours after the last dose of 77µg/ mL). Apart from supportive measures, the patient was successfully treated with intravenous N-acetylcysteine infusion during 11 consecutive days, and was discharged on day 34. The follow-up revealed full recovery of clinical and of laboratory findings of hepatic function. Comments: The paracetamol pharmacokinetics and pharmacodynamics in neonates and infants differ substantially from those in older children and adults. Despite the reduced rates of metabolism by the P-450 CYP2E1 enzyme system and the increased ability to synthesize glutathione - which provides greater resistance after overdoses -, it is possible to produce hepatotoxic metabolites (N-acetyl-p-benzoquinone) that cause hepatocellular damage, if glutathione sources are depleted. Paracetamol clearance is reduced and the half-life of elimination is prolonged. Therefore, a particular dosing regimen should be followed due to the toxicity risk of cumulative doses. This report highlights the risk for severe hepatotoxicity in neonates after paracetamol multiple doses for more than two to three days.